2017
DOI: 10.1186/s12864-016-3386-7
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale transcriptome comparison of sunflower genes responsive to Verticillium dahliae

Abstract: BackgroundSunflower Verticillium wilt (SVW) is a vascular disease caused by root infection with Verticillium dahliae (V. dahlia). It is a serious threat to the yield and quality of sunflower. However, chemical and agronomic measures for controlling this disease are not effective. The selection of more resistant genotypes is a desirable strategy to reduce contamination. A deeper knowledge of the molecular mechanisms and genetic basis underlying sunflower Verticillium wilt is necessary to accelerate breeding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 57 publications
9
36
0
Order By: Relevance
“…The pathways of plant-pathogen interaction and flavonoid biosynthesis were also induced in sunflower plants infected with V. dahliae [16], and the results were also consistent with those of Tan [27], who reported that most DEGs in tomato were associated with phenylpropanoid metabolism and plantpathogen interaction pathways. However, the glutathione metabolism pathway has rarely been reported in the transcriptome of cotton plants treated with V. dahliae.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The pathways of plant-pathogen interaction and flavonoid biosynthesis were also induced in sunflower plants infected with V. dahliae [16], and the results were also consistent with those of Tan [27], who reported that most DEGs in tomato were associated with phenylpropanoid metabolism and plantpathogen interaction pathways. However, the glutathione metabolism pathway has rarely been reported in the transcriptome of cotton plants treated with V. dahliae.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, DEGs related to JA, ET, SA, BR and cytokinin were induced in cotton plants treated only with CEF-082. The 8 plant hormones were also induced after infection with V. dahliae in sunflower [16]. The responses of the A. thaliana auxin receptors TIR1, AFB1 and AFB3 and auxin transporter AXR4 were impaired upon infection with V. dahliae [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MIPs have a main role in water and solute transport and aid in homeostasis during plant stress responses (Afzal et al, 2016). Recently, transcriptome data provided important clues about the involvement of MIPs in host-pathogen interactions (Galindo-Gonzàlez and Deyholos, 2016; Reeksting et al, 2016; Guo et al, 2017). Although there has been no study on PMIPs, in the present study, we identified and characterized a total of 126 MIP homologues from the genomes of six Phytophthora species, which cause severe economic losses because of devastating effects on numerous agriculturally and ornamentally important plants (Tyler et al, 2006; Haas et al, 2009; Lamour et al, 2012; Thines, 2014; Fawke et al, 2015; Derevnina et al, 2016; Wang et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, transcriptomic studies of the defense responses of plants infected with V. dahliae have become increasingly common, and several signal transduction pathways and key genes have been identified, including those involved in plant hormone signal transduction, plantpathogen interaction, and phenylpropanoid-related and ubiquitin-mediated signals in cotton; additionally, these studies have investigated members of key regulatory gene families, such as receptor-like protein kinases (RLKs), WRKY transcription factors and cytochrome P450s (CYPs) [3]. The expression levels of phenylalanine ammonia-lyase (PAL), 4-coumarate-CoA ligase (4CL), cinnamyl alcohol dehydrogenase (CAD), caffeoyl-CoA O-methyltransferase (CCoAOMT), and caffeoyl O-methyltransgerase (COMT) in the phenylalanine metabolism pathway have been shown to be upregulated in sea-island cotton [2]; the expression levels of 401 transcription factors (TFs), mainly in the MYB, bHLH, AP2-EREBP, NAC, and WRKY families, have been shown to be up-or downregulated in response to V. dahliae in Arabidopsis thaliana [15]; and genes encoding cyclic nucleotide gated channel (CNGC), respiratory burst oxidase homologue (RBOH), flagellin-sensitive 2 (FLS2), jasmonate ZIM domain-containing protein (JAZ), transcription factor MYC2, regulatory protein NPR1 and transcription factor TGA have been shown to be induced by V. dahliae in sunflower [16]. Several studies have investigated transcript levels in plants in response to biocontrol agents [17,18].…”
Section: Introductionmentioning
confidence: 99%